2020
DOI: 10.1038/s41598-020-65489-w
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus NS3 Protease Pharmacophore Anchor Model and Drug Discovery

Abstract: Zika virus (ZIKV) of the flaviviridae family, is the cause of emerging infections characterized by fever, Guillain-Barré syndrome (GBS) in adults and microcephaly in newborns. There exists an urgent unmet clinical need for anti-ZIKV drugs for the treatment of infected individuals. In the current work, we aimed at the promising virus drug target, ZIKV NS3 protease and constructed a Pharmacophore Anchor (PA) model for the active site. The PA model reveals a total of 12 anchors (E, H, V) mapped across the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…A natural active compound derived from black tea, theaflavin-3,3′-digallate, with an IC 50 of 2.3 µM was identified [ 28 ]. Asunaprevir and Simeprevir were identified using the pharmacophore anchor model to have potent anti-ZIKV activities with IC 50 values 4.7 µM and 0.4 µM [ 11 ]. Szymon et al identified small molecule inhibitors of ZIKV protease with a low micromolar affinity for protease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A natural active compound derived from black tea, theaflavin-3,3′-digallate, with an IC 50 of 2.3 µM was identified [ 28 ]. Asunaprevir and Simeprevir were identified using the pharmacophore anchor model to have potent anti-ZIKV activities with IC 50 values 4.7 µM and 0.4 µM [ 11 ]. Szymon et al identified small molecule inhibitors of ZIKV protease with a low micromolar affinity for protease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…After ZIKV and DENV infection of the host cell, the viral RNA is translated into a long polyprotein that is cleaved by a viral protease to generate three structural proteins (capsid, pre-membrane, and envelope proteins) and several nonstructural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5) that contribute to the formation of viral particles and replication of the viral genome [ 11 , 12 ]. The protease is an essential enzyme for viral replication and an attractive target for antiviral drug development [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies, such as high throughput screening (HTS), computation-guided drug design, and fragment based drug discovery have been applied to develop protease in-hibitors [129][130][131][132][133]. The available inhibitors have been reviewed thoroughly [10,33,117,[134][135][136][137][138][139].…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…The studies were published in 2017 (5/14; 36%), 41,42,[45][46][47] 2018-2019 (3/14; 21%), 43,44,54 and 2020-2021 (6/14; 43%). [48][49][50][51][52][53] The antiviral activities of the identified compounds were analyzed based on their ability to inhibit the NS2B-NS3 pro complex through protein thermal exchange assays (2/14; 14%), 41,45 T A B L E 1 Summary of chemical structures and biological proprieties of compounds with inhibitory activity against ZIKV NS2B-NS3 pro | 447 fluorescent peptide substrate assay (9/14; 65%), 42,44,[46][47][48][49][50]53,54 X-ray (1/14; 7%), 43 and fluorescence resonance energy transfer (2/14; 14%). 51,52 The IC 50 values for the inhibition of ZIKV NS2B-NS3 pro ranged at 0.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Part of the intermolecular interactions between the enzyme and compounds did not have a well-defined chemical bond. [41][42][43][44][45][46][48][49][50][51][52][53][54] In this context, 12 studies described the intermolecular interactions, such as hydrogen and hydrophobic bonds, involved in the activity of the compounds. 41,43,44,[46][47][48][49][50][51][52][53][54] Five compounds (Table 1, Entries 4, 5, 6, 7, and 17) showed the ability to interact with a region called 2B53 in NS3 (5/17, 29%), which contains essential amino acid residues to bind to NS2B.…”
Section: In Silico Studiesmentioning
confidence: 99%